Establishment of tissue culture protocol of Brassica Juncea var. BARI Sarisha-11 - Saha, Hridi Prova; Jawad, Alisa; Zaman, Samiha Nujhat; Roy, Asmita (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2024.